A Policy To Improve The Quality of UMN Alwasliyah Medan and Panca Budi Development University - Sibuea, Bismar; Lubis, Saiful Akhyar; Siahaan, Amiruddin; Ramadhani, Yulia R (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The purpose of this research is to describe the policies that Pancabudi Development University and UMN Alwasliyah Medan implement, the process by which policies are made, the manner in which policies are implemented, any variations in policy implementation, and the challenges that the institutions face in the field and how they resolve them. The present study employs a qualitative research methodology in conjunction with an empirical policy research strategy. By first outlining each policy at each site, doing an analysis inside each site, and then conducting an analysis between sites, this research used a multisite research design. The study's findings demonstrate that Pancabudi Development University has a policy for quality enhancement. 1) a rule requiring all UNPAB instructors and affiliated parties to promptly adapt to higher education standards without the chancellor's commands 2) Modify the metrics and raise the caliber of the literature produced by the instructors 3) Create a rewards program for instructors who successfully publish in journals approved by SINTA and Scopus. 4) Help instructors with their writing 5) Establish "study Saturdays," in which professors are allowed to study on Saturdays. 6) Give importance to the functional roles of lecturers 7) offer recognition and rewards to students who achieve well and engage in activities that enhance the campus's reputation; 8) adopt a philosophy inspired by Professor Khadirun Yahya that emphasizes unity. At Unpab, policy-making involves the bottom line. The challenges encountered are disparities in lecturers' writing skills, which Unpab addresses by offering support. Rules put in place by UMN Alwasliyah Medan 1) Implement academic directives without following the chancellor's instructions; Dikti's regulations are considered academy orders. 2) raise the standard of writing for both instructors and students; 3) publish student theses; 4) help instructors with their writing; 5) LPM UMN conducts frequent audits; and 6) the chancellor established an SMS center for direct complaints from all UMN inhabitants. 7) Online presence of instructors is tracked 8) UMN Alwasliyah's Foundation and Chancellor established a Code of Ethics Team. 9) honors the top instructors in Tridharma-related activities with awards 9) UMN fund handlers, like PTN-BH 10) Form a committee to revise the curriculum. 11) Letters on Alwasliyah philosophy in the same way as Shafs 10 and 11. At UMN, proposals are incorporated into the policy-making process by way of individual hierarchies. By approaching each lecturer differently, the challenges posed by misunderstanding and the shortcomings of some instructors in terms of modifying the writing standard were addressed.